Gold nanomaterials in the management of lung cancer - Guinart,A; Perry,HL; Wilton-Ely,JDET; Tetley,TD (Emerging Topics in Life Sciences, 2020)
Lung cancer (LC) is one of the most deadly cancers worldwide, with very low survival rates, mainly due to poor management, which has barely changed in recent years. Nanomedicines, especially gold nanomaterials, with their unique and size-dependent properties offer a potential solution to many challenges in the field. The versatility afforded by the shape, size, charge and surface chemistry of gold nanostructures allows them to be adapted for many applications in the diagnosis, treatment and imaging of LC. In this review, a survey of the most recent advances in the field is presented with an emphasis on the optical properties of gold nanoscale materials and their use in cancer management. Gold nanoparticle toxicology has also been a focus of interest for many years but the studies have also sometimes arrived at contradictory conclusions. To enable extrapolation and facilitate the development of medicines based on gold nanomaterials, it must be assumed that each design will have its own unique characteristics that require evaluation before translation to the clinic. Advances in the understanding and recognition of the molecular signatures of LC have aided the development of personalised medicines. Tailoring the treatment to each case should, ideally increase the survival outcomes as well as reduce medical costs. This review seeks to present the potential of gold nanomaterials in LC management and to provide a unified view, which will be of interest to those in the field as well as researchers considering entering this highly important area of research.